Simultaneous Determination of Five Alkaloids by HPLC-MS/MS Combined With Micro-SPE in Rat Plasma and Its Application to Pharmacokinetics After Oral Administration of Lotus Leaf Extract - Shuhan Zou; Shuhan Zou; Yuanyuan Ge; Yuanyuan Ge; Xuanhao Chen; Xuanhao Chen; Jin Li; Xuejing Yang; Xuejing Yang; Hui Wang; Hui Wang; Xiumei Gao; et al. (Frontiers Media S.A., 2019)
An environment-friendly and efficient method for simultaneous determination of five alkaloids (nunciferine, O-nornuciferin, liriodenine, armepavine, and pronuciferine) in rat plasma was established by HPLC-MS/MS associated with micro-solid phase extraction (micro-SPE). The plasma sample was pretreated by using micro-SPE columns filled with polymer materials PEP-2 and eluted by little organic solvent (400 µl acetonitrile). The five alkaloids were separated with acetonitrile and 0.1% formic acid aqueous solution on Eclipse plus C18 column. The mode of positive electrospray ionization was used to measure the analytes in multiple-reaction monitoring (MRM). The determination coefficients (R2) of the five alkaloids were greater than 0.99. The lower limit of quantification (LLOQ) of O-nornuciferin, liriodenine, and armepavine was 0.5 ng·ml−1, and that of nunciferine and pronuciferine was 1 ng·ml−1. The validated method was effectively used for the pharmacokinetics of the five orally administrated alkaloids of lotus leaf extract in rat plasma.